THE CONTENT OF THE REFORMS CARRIED OUT IN THE FIGHT AGAINST MONOPOLY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article provides detailed information on the ongoing reforms in the fight against aging and their essence: